Giant colonic diverticulum of the transverse colon as a rare cause of surgical acute abdomen: A case report - Shah, Bimal; Gore, Shivanjali; Singh, Divyanshu (Indian Journal of Case Reports, 2024)
A colonic diverticulum larger than 4 cm in size is referred to as a giant colonic diverticulum and is an uncommon occurrence. Globally,